(3TQM GdeLOjIs - (3GdefTGhj GdeUQj, YHO GdQGRbs
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdSeGA HQhLG aEf Yde GdejbGJ ef CLd aQhV GdcaGjGJ hChdi eG JfJgj Edjg cja dG hgh hSjdI deYQaI ChbGJ GdUdhGJ GdeaQhVGJ hGdefOhHGJ hGdhSGFd JTQa HTQa GdebGUO s
(3BNQgG (B:s
(3NGJeI aj eYQaI MGd GdchcH aj Cj hbJ aQV GdbGA eWGdY WdhYg ef cWGdY GdhbJ GdeaQhV aEf Hbj CcKQ ef bjhS XghQI cGedG agh JMJ GdCab hEf Hbj eKdg hGab GdaQGZs
(3JHUQI GdeDda (B:s
(3GdehbJ HOejGWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf (B2\728s
(3EjVGM Gdecfhf (B2\728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs